PENINGKATAN DAYA SAING MELALUI PLATFORM SHOPEE DENGAN ANALISIS SWOT (STUDI KASUS : MTRSTORE.ID) - Sahlul Haq Robbani; Aries Kurniawan (POLITEKNIK LP3I JAKARTA, 2025)
MTRSTORE.ID is a thrift shop business operating in the fashion industry, offering imported thrift products such as jeans, chinos, and cargo pants. This business was chosen due to the rapid trend growth in the sector, particularly among teenagers. This study aims to analyze the competitiveness of MTRSTORE.ID, a thrift shop operating on the Shopee e-commerce platform, using the SWOT analysis approach. In the context of globalization and advancements in information technology, businesses like MTRSTORE.ID face challenges to remain relevant and competitive in an increasingly tight market. The analysis results show that MTRSTORE.ID has strengths, including high sales potential through Shopee's large user base and attractive promotions. However, the business also faces weaknesses, such as intense competition and high administrative costs. Opportunities to boost sales include participating in discount programs and utilizing Shopee's advertising features, while threats such as price competition and challenges in maintaining product quality need to be addressed. This research employs a qualitative methodology with a case study approach. It recommends that MTRSTORE.ID implement these strategies to enhance its competitiveness on Shopee, utilizing the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis framework.